Mandarin essential oil as natural antipathogenic agent in foodborne disease - Blázquez, María Amparo (2013)
Microbial biofilms are an important problem in food and pharmaceuti- cal industries, being responsible of principal foodborne disease. Bio- films have been implicated in serious humans infections and are responsible of 90% of chronic infections. Bacterial biofilms are com- plex communities of bacteria embedded in a self-produced matrix and attached to inert or living surfaces. These microorganism communities are more resistant to both antibiotics and immune system. Spices in food products are mainly used to enhance flavour and taste, and in this sense the essential oils obtained from spices or Citrus genus could be applied as natural food preservatives. The aim of the present study was to determine the chemical composition of mandarin (Citrus reticu- lata Blanco, Rutaceae) essential oil and evaluate their activity against bacterial growth and biofilm formation of Pseudomonas aeruginosa ATCC2783. A total of 41 compounds accounting for 99.34% of man- darin essential oil were identified by GC/MS analysis. The monoter- pene hydrocarbons limonene (89.82%) followed by g-terpinene (2.76%) and myrcene (2.51%) were the main compounds. Mandarin essential oil at 1, and 0.1 mg/ml, did not inhibit Pseudomonas aeru- ginosa growth, however at these same doses the inhibition of bacterial biofilm formation was 72% and 50% respectively. The results obtained with the lower dose was similar to azithromycin at 5 lg/ml used as positive control. Natural compounds controlling bacterial virulence fac- tors such as biofilm formation are interesting to prevent the develop- ment of resistant strains (Otto, FEMS Microbiol Let 2004; 241:135?141).Our results show that mandarin essential oil could be used as antipathogenic agent in food.